Observations and modeling of energy distributions in the spectra of young stars - Manapbayeva, A.B.; Kuratova, A.K.; Kuratov, K.S.; Alimgazinova, N.Sh.; Komesh, T.; Demesinova, A.M.; Naurzbaeva, A.Zh.; Kyzgarina, M.T. (Recent Contributions to Physics, 2019)
Investigation of young stars is one of the main directions in astrophysics. Firstly, it is related to the fact that these studies allow us to learn more about the star, about the process of formation and evolution of stars and planets. Astronomers of the different countries carried out that kind of study, however there are still some questions are not clear, in particular, the physical characteristics of young nonstationary stars and certain details of their evolution. The work shows spectral and photometric observations of Herbig's Ae / Be young stars. The distribution of energy in their spectra was studied based on the photometric data obtained and available in the literature, as well as the results of modeling. As a result of the study of the star IRAS 22150 + 6109, emission features in the spectrum of the star were determined, the geometric characteristics of its protoplanetary disk were determined. In this article, photometric data from specialized catalogs and observational data were used at the Assy-Turgen observatory and at the Tien-Shan astronomical observatory of the Astrophysical Institute named after V.G. Fesenkov (APhIF). The object of the study are the young stars Ae / Be Herbig. The research results can be used in astronomy, cosmology, theoretical physics and computational astrophysics.